Strategies For Improving The Quality Of Driver's License (SIM) Issuance Services At Pringsewu Police Resort Based On A Public Management Perspective - Rahayu Laili; Tina Miniawati Barusman Virgawenda (Citakonsultindo, 2026)
The Pringsewu Police Resort is obligated to maintain service quality throughout the entire process of driver's license (SIM) issuance, starting from registration, data verification, theoretical and practical examinations, to the issuance of the license, in order to ensure that services are transparent, fast, accountable, and in accordance with established public service standards. To identify aspects that still require improvement in SIM issuance services, the Pringsewu Police Resort collects various complaints and feedback from the public through suggestion boxes and online complaint channels. These data serve as an important source for understanding users' real service experiences and for describing the most frequently encountered problems in the service process. The method used in this study is a descriptive method, which aims to accurately describe the conditions of the research object based on data obtained from interview transcripts, field notes, photographs, video recordings, personal documents, notes or memos, and other official documents. The approach employed in this research is an inductive approach, namely drawing conclusions based on empirical facts found in the field. The results of this study indicate that the quality of SIM issuance services at the Pringsewu Police Resort has generally been fairly good when viewed from the aspects of input, process, and output. Nevertheless, several obstacles remain, particularly limitations in human resources, facilities and infrastructure, long queues, and relatively complex service procedures, which affect service effectiveness and efficiency. To improve service quality, strategies are needed that focus on strengthening human resources, improving facilities, simplifying service procedures, enhancing internal coordination, and using information technology. These strategies are expected to increase public satisfaction through faster, more transparent, and more responsive SIM issuance services.